Fast ReRouting Flow-based Model with Implementation of Path Protection - Yeremenko, O.; Yevdokymenko, M.; Sleiman, B.; Omowumi Stephen Olayinka (My University, 2020)
In this paper, the fast rerouting model with the implementation of the path protection scheme in the infocommunication network is investigated. Within the proposed Fast ReRoute model with the path protection schemes, the problem of calculating the set of primary and backup disjoint paths was solved. The advantage of the improved model is the possibility of implementing protection schemes 1:1, 1:2, ..., 1:n without introducing an additional set of routing variables. This results in reducing the dimension of the optimization problem to be solved and the computational complexity of its implementation. The optimality criterion of routing solutions contributes to the formation of primary and backup disjoint paths with the maximum bandwidth. Additionally, the path with the highest bandwidth will correspond to the primary path, while the rest of the paths will be used as a backup in decreasing order of their bandwidth.
Keywords: Fast ReRouting; path protection; disjoint paths; bandwidth; optimization